Konsep Taukil Wali Nikah dalam Kitab Fiqih Ala Mazahibil Arba’ah Karya Syeikh Abdurrahman al-Jazairi - Muhammad, Nashih; Murtadho, Murtadho; Sariyekti , Eko (El-Qenon: Journal of Islamic Law, 2024)
Taukil or al-wakalah is the act of handing over one's affairs to another person (deputy) to carry out a certain task or business. Then, the representative takes the position of representing (muwakkil) the rights and obligations that apply as long as the muwakkil is still alive. Islamic jurisprudence experts agree that taukil wali is valid and permissible because it aims to help and support each other based on the values of goodness and piety. Wali Mujbir can represent the marriage contract either with or without the permission of his daughter, while women who are widows cannot be forced to do so. The representative must declare himself as a representative of the representing party. The requirements for a representative are to be male, Muslim, mature, independent and fair (not wicked). Three schools of thought argue that Taukil is carried out by the guardian, either mujbir or ghiru mujbir. Meanwhile, the Hanafi School believes that taukil can be performed by women who have reached puberty, whether they are still virgins or widows. Three schools of thought state that representatives must obtain permission from the woman, except the Maliki school of thought which does not require permission